Disfunción miccional en el adulto. Un artículo docente - Valdevenito S, Juan Pablo; Olea C, Mauricio; Moya G, Francisco; Lizana V, Pablo; Toro M, Hugo; Baloian C, Simon (Revista Hospital Clínico Universidad de Chile, 2021)
Voiding dysfunction is defined as an abnormally slow and/or incomplete micturition, and canbe divided in bladder outlet obstruction (BOO) and detrusor underactivity (or hypocontractility).BOO is characterized by reduced urine flow rate and increased detrusor pressure, and can beof anatomical or functional origin. Detrusor underactivity encompasses a reduced urine flow rateassociated to low pressure and/or poorly sustained detrusor contraction, and its etiology ismultifactorial. Lower urinary tract symptoms are classified as storage, voiding and post micturitionsymptoms, may be objectively quantified with specific questionnaires, and don’t correlateproperly with voiding dysfunction. Patients’ evaluation requires a directed physical examination ofthe abdomen, pelvis and genitals focused to detect anatomical and neurological abnormalities.Voiding dysfunction can be demonstrated non-invasively using uroflowmetry and pelvic ultrasound.Uroflowmetry allows determining urinary flow characteristics and their most important parametersare voided volume, maximum flow rate and shape of the curve. Pelvic ultrasound permits toestimate prostatic size and post void residual, suspect detrusor hypertrophy (due to BOO) anddetect bladder stones. Invasive test must be reserved for special cases of confirmed voidingdysfunction: cystoscopy when there is concomitant hematuria, urethrocystography to studyurethral stenosis and urodynamics to differentiate BOO from detrusor underactivity.